Flocculation of oil sands tailings by hyperbranched functionalized polyethylenes (HBfPE). (July 2017) - Botha, Linda; Davey, Stepheney; Nguyen, Benjamin; Swarnakar, Anindya K.; Rivard, Eric; Soares, João B.P.
Highlights: We used novel HB f PE with different functional contents to flocculate tailings. The HB f PE performance improved with increasing functional contents. The HB f PE required significantly less mixing than the reference PAM. The HB f PE generated more compact sediments that were easier to dewater. Abstract: We synthesized a series of hyperbranched functional polyethylene (HB f PE) flocculants with functional group contents ranging from 30 and 50 mol%, and used them to flocculate oil sands mature fine tailings (MFT). MFTs (diluted to a concentration of 20 wt%) treated with the novel HB f PE had higher settling rates, lower capillary suction time (CST), and lower turbidity than when treated with a reference polyacrylamide (PAM). Within the HB f PE series, the settling performance improved when the functional group content in the copolymer increased. When combined with centrifugation, the HB f PE flocculants generated sediments with higher solids contents than PAM within a shorter centrifugation time. This may be attributed to the tendency of HB f PE to form smaller flocs that compact more tightly than PAM. Floc development for HB f PE and PAM was compared with focused beam reflectance measurement (FBRM). While floc formation with HB f PE and PAM was similar, it required significantly less mixing energy for optimal performance, due to the significantly lower molecular weight (<10, 000 g/mol) of HB f PE.